1994
DOI: 10.1152/jn.1994.71.5.1862
|View full text |Cite
|
Sign up to set email alerts
|

Proprioceptive coordination of movement sequences: discrimination of joint angle versus angular distance

Abstract: 1. The purpose of these experiments was to determine the accuracy with which human subjects could discriminate proprioceptive (nonretinotopic) targets during movement. The targets were located at either a specified angle in joint space, or a specified angular distance from an initial joint angle. 2. In these experiments the right elbows of normal human subjects were passively extended from either predictable or unpredictable starting angles. The subjects were instructed to open the right hand to indicate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 0 publications
2
20
0
1
Order By: Relevance
“…The resolution of externally powered rotators is not governed by the mechanical components but by the accuracy of the user's control input. The static joint angle resolution of intact humeral rotation has been reported to be 3.3°, with a dynamic resolution of 8.1° [25]. Thus, when considering the accuracy of the proposed controller in contrast to physiological resolution, we expect that the patient will perceive little difference between their voluntarily selected bone angle and the output angle of the prosthetic rotator.…”
Section: Discussionmentioning
confidence: 98%
“…The resolution of externally powered rotators is not governed by the mechanical components but by the accuracy of the user's control input. The static joint angle resolution of intact humeral rotation has been reported to be 3.3°, with a dynamic resolution of 8.1° [25]. Thus, when considering the accuracy of the proposed controller in contrast to physiological resolution, we expect that the patient will perceive little difference between their voluntarily selected bone angle and the output angle of the prosthetic rotator.…”
Section: Discussionmentioning
confidence: 98%
“…Signals of both position and velocity are used to execute movement (22). Sensation of these signals has usually been measured by matching the position of homologous joints on both sides of the body or detecting applied movements and their direction.…”
Section: Sensations Of Loint Position and Movementmentioning
confidence: 99%
“…Previous studies have reported that the central nervous system (CNS) is more accurate in processing end-point control variables than joint excursion variables for kinesthetic-related movements [20, 21]. Mechanoreceptors relay information related to kinesthesia to the CNS; therefore, appropriate joint configurations should facilitate accurate haptic perception during motor tasks.…”
Section: Discussionmentioning
confidence: 99%